ANALYSIS FLOOD AND CHANNEL CAPACITY IN SUB DRAIN SAWOJAJAR OF BANGO WATERSHED MALANG - Sang Putu Dhika Purnama; Mona Sintha Safitri (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2026)
Global climate change has intensified extreme rainfall in Malang City, leading to frequent inundation in the Sawojajar area, particularly along Jl. Danau Kerinci to Jl. Danau Sentani Raya. This study aimed to analyze the existing drainage system's capacity and redesign channel dimensions using EPA SWMM 5.2 simulation. Data utilized included 10-year rainfall records (2015-2024) from three stations (Ciliwung, Jabung, Sukun) and primary field data. Design rainfall, calculated via Log Pearson Type III and validated, was 129.394 mm/day for a 10-year return period. Simulation results indicated that existing drainage segments (H to M), with capacities ranging from 0.732 m³/s to 0.846 m³/s, were unable to accommodate the 10-year return period design discharge (1.464 m³/s to 2.829 m³/s), necessitating redesign. The redesigned segments implemented 100 cm x 120 cm U-Ditch channels (105 cm effective height), which successfully increased flow capacity (2.772 m³/s to 3.201 m³/s) and prevented overflow for the 10-year return period. However, these dimensions proved insufficient for a 25-year return period. The estimated total cost for this drainage reconstruction is Rp 2,001,282,000.00. This research offers technical recommendations for improving urban drainage and fostering flood-resilient infrastructure.